2023
DOI: 10.1038/s41598-023-42144-8
|View full text |Cite
|
Sign up to set email alerts
|

A thioacetamide-induced liver fibrosis model for pre-clinical studies in microminipig

Kotaro Nishi,
Hiroshi Yagi,
Mana Ohtomo
et al.

Abstract: Drug-induced liver fibrosis models are used in normal and immunosuppressed small animals for transplantation and regenerative medicine to improve liver fibrosis. Although large animal models are needed for pre-clinical studies, they are yet to be established owing to drug sensitivity in animal species and difficulty in setting doses. In this study, we evaluated liver fibrosis by administering thioacetamide (TA) to normal microminipig and thymectomized microminipig; 3 times for 1 week (total duration: 8 weeks).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…From the viewpoint of clinical applications, Katsuda et al recently successfully established human hepatocyte progenitors from human infant hepatocytes [ 40 ]. In addition, pre-clinical transplant experiments using existing large animal models of cirrhosis are necessary for real-world clinical implementation [ 41 ], hence our study demonstrated the potential of decellularized scaffolds with CLiPs as grafts for transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…From the viewpoint of clinical applications, Katsuda et al recently successfully established human hepatocyte progenitors from human infant hepatocytes [ 40 ]. In addition, pre-clinical transplant experiments using existing large animal models of cirrhosis are necessary for real-world clinical implementation [ 41 ], hence our study demonstrated the potential of decellularized scaffolds with CLiPs as grafts for transplantation.…”
Section: Discussionmentioning
confidence: 98%